My Big Picture Wordbook At School - "NA" (Noida Brijbasi Art Press, 2006)
It is a series of beautifully illustrated picture wordbooks, which help young children to associate words with objects in their day-to-day life. Sally and Sam, two delightful characters, accompany the children in their journey from one colourful destination to another.
Keywords: Big activity book